Aluminum-Induced Alterations to the Cell Wall and Antioxidant Enzymes Involved in the Regulation of the Aluminum Tolerance of Chinese Fir (Cunninghamia lanceolata) - Xu, Shanshan; Wu, Lihua; Li, Lingyan; Zhong, Minghui; Tang, Ying; Cao, Guangqiu; Lin, Kaimin; Ye, Yiquan (Frontiers in Plant Science, 2022)
Chinese fir (Cunninghamia Lanceolata), which is an important coniferous tree species in China, mainly planted in acid soils and suffered from serious Aluminum (Al) toxicity. However, Al toxicity and its resistance mechanism in Chinese fir remain largely unknown. In this study, the Al-induced modification and possible role of cell wall in regulating Al tolerance in Chinese fir were investigated by using seedlings with contrasting Al tolerance, namely, Al-sensitive (YX02) and Al-resistance (YX01) genotypes. The results in present work showed that Al treatment resulted in a dose and time dependent inhibition of root growth and oxidative damage in both genotypes, with a more serious root inhibition and oxidative damage observed in YX02 as compared with YX01. The severe oxidative damage observed in YX02 under Al stress was found to correlate with lower anti-oxidant enzymes as compared with YX01. While the serious root growth inhibition observed in YX02 compared with YX01 was found to associated with higher accumulation of Al in pectin and hemicllulose 1 (HC1) fraction, which resulted from higher pectin and HC1 contents while lower degree of pectin demethylation due to increasing pectin methylesterase activity in YX02, and ultimately enhanced cell wall binding capacity for Al in YX02. Taken together, our results suggested that enhancement of anti-oxidant enzymes and cell wall modification-induced Al exclusion are the two mechanisms that confer Al tolerance in genotypes of Chinese fir.